Aristotle and Menander on the ethics of understanding - Cinaglia, Valeria. (Philosophia Antiqua, 2015)
In Aristotle and Menander on the Ethics of Understanding , Valeria Cinaglia offers a parallel study of Menander's New Comedy and Aristotle's philosophy focusing on subjects ranging from epistemology and psychology to ethics. Cinaglia does not aim to demonstrate the direct philosophical influence of Aristotle on Menander, but explores the hypothesis that there are significant analogies between the two that disclose a shared thought-world. Cinaglia shows that Aristotle and Menander offer analogous views of the way that perceptions and emotional responses to situations are linked with the presence or absence of ethical and cognitive understanding, or the state of ethical character development: the study of these analogies contributes to a deeper understanding of both frameworks involved.